Characterisation of nitrogen-containing organic compounds by UHPLC-Qtof-MS and anti-amylase activity from the chloroform extract of the bark of Rhizophora mucronata - P. Resmi; G. Jitha; Vishnu Murali; Anu Gopinath (SpringerOpen, 2021)
Abstract Background Medicinal importance of mangrove plant Rhizophora mucronata, a red mangrove species found in the Asian countries, has long been recognised in traditional systems of medicine. The identification of its phytoconstituents can be a starting point for the drug development. The aim of the work was to extend the current knowledge of phytoconstituents from R. mucronata and to explore its pharmacological importance in the treatment of diabetes mellitus. In the present study, we analysed the chloroform extract from the bark of the mangrove plant R. mucronata for nitrogen-containing constituents using UHPLC QTOF MS profiling, and α-amylase inhibition assay was carried out. Results Four nitrogen-containing compounds were identified from the chloroform extract of the bark of R. mucronata using UHPLC QTOF MS profiling. The compounds identified were N,N'-dicyclohexyl urea, a cryptolepine derivative (C17H15N3O), an aliphatic cyclic compound with hydroxyl and amino groups (C22H43NO), and C16H19NO2 (m/z 258.1495). The anti-amylase activity, an in vitro antidiabetic bioassay, of chloroform extract showed an IC50 value of 220.09 μg/ml. Conclusions This is the first report on the identification of nitrogen-containing compounds from the chloroform extract of the bark of the R. Mucronata. One of the compounds identified was a novel cryptolepine derivative (C16H13N3O), and it falls under the rare category indoloquinoline alkaloid. The chloroform extract also showed significant activity towards α-amylase inhibition assay. Thus, the study has gone some way towards our understanding of the efficacy of bark of the R. mucronata for the treatment of diabetes mellitus and is open for further research.